Drama as Arts-Based Pedagogy and Research: Media Advertising and Inner-City Youth - Conrad, Diane (Alberta Journal of Educational Research, 2002)
This reflective practice case study involved creating and delivering a unit for inner-city high school students that integrated drama and media literacy/production with a focus on advertising. It used socially critical or issues-based drama to examine the relationship between youth and media: to draw out and question and have them question their meanings or understandings of advertising. Interpretation of students' responses to the work and the ad messages they created saw these young people as sophisticated readers of advertisements who made meanings that spoke to their needs, desires, and life experiences. The study used drama in all stages as an arts-based approach to generating, interpreting, and representing research. Significant teaching-learning moments that occurred during the work with students are depicted through a set of scripted vignettes.